Laparoscopic technique of para-aortic lymph node dissection: A comparison of the different approaches to trans- versus extraperitoneal para-aortic lymphadenectomy - Soshi Kusunoki; Kuan-Gen Huang; Angelito Magno; Chyi-Long Lee (Wolters Kluwer Medknow Publications, 2017)
Since Dr Dargent first reported endoscopic surgery using retroperitoneal pelvicoscopy to perform pelvic lymph node sampling in 1987, many literature reviews on the safety and feasibility of laparoscopic staging surgery of gynecologic malignancies have been published. However, the procedure of laparoscopic lymphadenectomy is more difficult to perform due to the limited surgical space and associated technical problems. Especially in the para-aortic lymphadenectomy procedure, there are many barriers to overcome in the surgical field, learning curve, and technique. We present a review of lymphadenectomy, especially para-aortic lymphadenectomy.